Modeling of Co-Creation in the Adventure Tourism: Empowering the Role of Customer Participation to Strengthen Behavioral Intention (Best Practice: Tourism Village Nglangeran - Gunung Kidul DIY) - Sri Ismulyati; Hubertina Karolina Ngarbingan; Ginta Ginting (AIBPM Publisher, 2022)
Adventure tourism is one of the sectors that undergoes a rapid growth with potential market that is estimated to provide 9% of GDP of a country. However, the great opportunity has not yet to be optimized by business doers, particularly in Indonesia, whereas invisibly Indonesia has natural resources that can be managed well to offer adventure tourism. In short, business doers particularly in tourism field are challenged to encourage the growth of adventure tourism. Therefore, this paper suggests a conceptual model of co-creation by involving customer participation to explore facts on field on how far the role of consumer involvement as co-producer in creating value (unique experience). Co-creation becomes the key success of adventure tourism that is still becoming a phenomenon and research gap that needs further evidence. Value co-creation by involving consumers to participate will encourage satisfaction and revisit intention that will impact on business sustainability. The paper proposes conceptual model developed on the basic of empirical study and can be used to conduct research in the development of tourism industry. Preliminary research (obsevation) has been conducted in the Special Region of Yogyakarta (DIY), namely: Nglanggeran Tourism Village (Gunung Kidul Regency). This tourist village represents the spectrum of integrative development of tourism and the creative economy producing attractive and creative adventure. Empirically the objective proposing this modeling can provide trigger to develop further research on value co-creation by referring to service dominant logic paradigm especially in the tourism sector. Keywords: Adventure Tourism, Behaviour, Co-creation Value, Customer Participation, Experience.